Emotional challenges in reforming transitional criminal justice in Ukraine: the role of subsidiarity and European directives in deterring criminalization (research hypothesis) - Туляков, Вячеслав Олексійович; Туляков, В. О.; Tuliakov, Viacheslav O. (My University, 2024)
To identify the need to reform Ukraine's transitional criminal justice system in the post-war context, taking into account public emotions such as anger, fear and the need for justice in the context of European integration. Research will examine how emotions influence criminal policy reform in post-war Ukraine, assessing the role of European directives in the context of the principles of subsidiarity and proportionality in curbing excessive criminalisation. The project explores the emotional challenges associated with reforming transitional criminal justice in Ukraine in the post-war context. It meets the current needs of the state, in particular, against the backdrop of European integration and social transformations taking place after the military conflict. An in-depth analysis of the emotional impact on criminal policy allows us to create a more effective and fair justice system, which is an important element of Ukraine's post-war recovery. The research offers solutions to important social problems, including social exclusion and post-war trauma, control of organized crime, and corruption. The project focuses on how emotional factors (fear, anger, need for justice) influence public demands for criminal policy and implementing fair punishments. Визначити необхідність реформування перехідної системи кримінального правосуддя України в післявоєнному контексті, враховуючи суспільні емоції, такі як гнів, страх і потреба у справедливості в контексті європейської інтеграції. Дослідження вивчатиме, як емоції впливають на реформу кримінальної політики в післявоєнній Україні, оцінюючи роль європейських директив у контексті принципів субсидіарності та пропорційності у стримуванні надмірної криміналізації. Проект досліджує емоційні виклики, пов’язані з реформуванням перехідного кримінального правосуддя в Україні в післявоєнному контексті. Це відповідає актуальним потребам держави, зокрема, на тлі євроінтеграції та суспільних трансформацій, що відбуваються після військового конфлікту. Глибокий аналіз емоційного впливу на кримінальну політику дозволяє створити більш ефективну та справедливу систему правосуддя, що є важливим елементом післявоєнного відновлення України. Дослідження пропонує вирішення важливих соціальних проблем, зокрема соціальної ізоляції та післявоєнної травми, боротьби з організованою злочинністю та корупцією. Проект зосереджується на тому, як емоційні чинники (страх, гнів, потреба справедливості) впливають на суспільні вимоги щодо кримінальної політики та впровадження справедливих покарань.
Емоційні виклики в реформуванні транзитивної кримінальної юстиції України: роль субсидіарності та європейських директив у стримуванні криміналізації
Tuliakov V. O. Emotional challenges in reforming transitional criminal justice in Ukraine: the role of subsidiarity and European directives in deterring criminalization (research hypothesis) / V. O. Tuliakov // ResearchGate. - preprint. - 2024. - 10 р. Режим доступу: DOI:10.13140/RG.2.2.35921.75365
Keywords: реформування транзитивної кримінальної системи України; кримінальна політика у повоєнній Україні; емоційна реакція населення; субсидіарність; емоційні виклики; військовий конфлікт; європейські принципи кримінальної політики; транзитивне правосуддя; соціальна справедливість; reform of the transitive criminal system of Ukraine; criminal policy in post-war Ukraine; emotional reaction of the population; subsidiarity; emotional challenges; military conflict; European principles of criminal policy; transitive justice; social justice